Crystal structure of the DNA sequence d(CGTGAATTCACG)2 with DAPI. Issue 9 (6th September 2017) - Sbirkova-Dimitrova, Hristina I.; Shivachev, Boris
Abstract : The interaction of DAPI with d(CGTGAATTCACG) results in displacement of the ordered spine waters and confers hydrophobic behaviour on the DNA. Abstract : The structure of 4′, 6‐diamidine‐2‐phenylindole (DAPI) bound to the synthetic B‐DNA oligonucleotide d(CGTGAATTCACG) has been solved in space group P 21 21 21 by single‐crystal X‐ray diffraction at a resolution of 2.2 Å. The structure is nearly isomorphous to that of the previously reported crystal structure of the oligonucleotide d(CGTGAATTCACG) alone. The adjustments in crystal packing between the native DNA molecule and the DNA–DAPI complex are described. DAPI lies in the narrow minor groove near the centre of the B‐DNA fragment, positioned over the A–T base pairs. It is bound to the DNA by hydrogen‐bonding and van der Waals interactions. Comparison of the two structures (with and without ligand) shows that DAPI inserts into the minor groove, displacing the ordered spine waters. Indeed, as DAPI is hydrophobic it confers this behaviour on the DNA and thus restricts the presence of water molecules.